1996
DOI: 10.1111/j.1532-950x.1996.tb01371.x
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Cord Swelling as a Myelographic Indicator of Prognosis: A Retrospective Study in Dogs With Intervertebral Disc Disease and Loss of Deep Pain Perception

Abstract: The association of myelographic spinal cord swelling with neurological outcome was examined in 46 dogs with intervertebral disc disease and absence of deep pain perception (DPP). Spinal cord swelling was measured by calculating a ratio of the length of the loss of the myelographic dye column to the length of the second lumbar vertebra (L2). A positive neurological outcome was defined as return of voluntary motor function. A cut-off value for swelling:L2 of 5.0 was established by the creation of a receiver oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
102
0
11

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(125 citation statements)
references
References 16 publications
10
102
0
11
Order By: Relevance
“…Our data support the consensus from previous studies indicating that presence or absence of CPP is the most important prognostic factor for functional recovery from SCI 5, 6, 12, 13, 14, 15. Indeed, we found that loss of CPP seems to be an indicator for poor recovery in dogs with L4‐S3 SCI (1/13 dogs recovered within 3 weeks, and 3/11 had a long‐term successful outcome).…”
Section: Discussionsupporting
confidence: 91%
“…Our data support the consensus from previous studies indicating that presence or absence of CPP is the most important prognostic factor for functional recovery from SCI 5, 6, 12, 13, 14, 15. Indeed, we found that loss of CPP seems to be an indicator for poor recovery in dogs with L4‐S3 SCI (1/13 dogs recovered within 3 weeks, and 3/11 had a long‐term successful outcome).…”
Section: Discussionsupporting
confidence: 91%
“…Considering the difficulty of objectively establishing the extent of the spinal cord damage, it is generally accepted to use the absence of pain perception as the most important indirect sign to asses complete functional spinal cord transection 1, 5. Absence of pain perception is classically associated with a severe to poor prognosis for functional recovery of voluntary locomotion 2, 6, 7, 8, 9. A recent study on paraplegic TL dogs with absent pain perception due to IVDE did not identify prognostic factors for any of the investigated variables, including age, corticosteroid administration, early surgical treatment, and severity of compression 10.…”
mentioning
confidence: 99%
“…Outros estudos demonstraram uma variação de 25% a 100% de recuperação considerada satisfatória em cães paraplégicos e sem PDP (Duval et al 1996, Laitinen & Puerto 1998, Scott & Mckee 1999, Olby et al 2003, Kazakos et al 2005, Arias et al 2007, Festugatto et al 2008. No estudo de Arias et al (2007), os oito cães sem PDP voltaram a caminhar, sendo cinco sem seqüelas neurológica e três com ataxia proprioceptiva.…”
Section: Resultsunclassified
“…No estudo de Arias et al (2007), os oito cães sem PDP voltaram a caminhar, sendo cinco sem seqüelas neurológica e três com ataxia proprioceptiva. Várias são as justiϐicativas para explicar as diferenças nas taxas de recuperação (Duval et al 1996, Laitinen & Puerto, 1998, porém, neste estudo, o baixo número de casos e a diϐiculdade em determinar e estimar a duração da perda da PDP contribuiu para o resultado. Kazakos et al (2005) questionaram o valor prognóstico da ausência da PDP em cães com DDIV toracolombar devido à interpretação subjetiva e veriϐica-ram que a velocidade da perda dos movimentos voluntá-rios é mais precisa e o prognóstico é mais favorável para aqueles com perda progressiva da função motora.…”
Section: Resultsunclassified
See 1 more Smart Citation